Influence of work-life balance and job stress to employee performance mediated by job satisfaction on millenial employees - Amelia, Fadillah Rizky; Heriyadi, Heriyadi; Daud, Ilzar; Shalahuddin, Ahmad; Sulistiowati, Sulistiowati (Institute of Computer Science (IOCS), 2023)
The purpose of this study was to determine and analyze the effect of work-life balance and job stress on employee performance mediated by job satisfaction in millennial employees in the finance department of state-owned companies in Indonesia, the companies studied were PT Jasaraharja. The method and approach used in this research is descriptive quantitative with an associative causal level of explanation. The sample used in this study amounted to 213 samples, namely millennial generation employees ranging in age from 26-42 years. Sampling technique through a survey using a questionnaire distributed via social media using a Likert scale as a measure. Structural Equation Modeling (SEM) through AMOS 24 was employed for model analysis in this research. The results of this study prove that there is a significant influence between work-life balance and job stress on employee performance. and analysis of the mediating variable proves that there is an indirect influence between work-life balance and job stress on employee performance through job satisfaction. this research is expected to overcome the problems of work-life balance and job stress for millennial employees and through this research it is hoped that PT. Jasaraharja can increase employee job satisfaction.